Recent Applications of Cyclodextrins as Food Additives and in Food Processing - Martina, Katia; Binello, Arianna; Lawson, Dale; Jicsinszky, Laszlo; Cravotto, Giancarlo (Current Nutrition & Food Science, 2013)
Nowadays the application of cyclodextrin-assisted molecular encapsulation in foods offers many advantages. Cyclodextrins, their derivatives and their cross-linked polymers can all improve the quality of food in storage, remove specific components and stabilize and increase the presence of components that are important for a healthy diet. The application of cyclodextrins and their complexes in packaging materials can help not only transport of previously nontransportable foods, but may also prevent, or at least decelerate, the spread of microbial infections. The number of publications, particularly analytical papers, on this matter is constantly increasing. Although the application of modern analytical methods and equipment allows for the quantitation of previously subjectively characterized parameters, bio-sensory methods are still important. The application of cyclodextrins in the nutraceutical industry has many advantages; however, some side effects connected with the inclusion complexation ability of these carbohydrates should lead scientists to study cases on an individual basis. Recent developments in the major fields of cyclodextrin related food research are herein summarized.
Keywords: food additives